2017
DOI: 10.1039/c6ra25892a
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium oxide-based photochromic composite film

Abstract: V2O5-based composite films were fabricated using peroxo-iso-poly vanadic acid as the filler and transparent urethane resin as the matrix, and the resulting composite films exhibited photochromic property when irradiated with ultraviolet (UV) light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…Recent reports also reveal that vanadium compounds can be fatal in many cases and therefore such applications should be carried out under extreme precautions along with unfailing protections . V 2 O 5 is a versatile material and also find extensive applications in chemical sensing, electro‐chromic and optical switching devices . V 2 O 5 in various forms as well as its nanocomposites are at present being widely employed as intercalation material in rechargeable batteries with mono/multivalent ions such as Li + , Na + , Mg 2+ ions, etc ,…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports also reveal that vanadium compounds can be fatal in many cases and therefore such applications should be carried out under extreme precautions along with unfailing protections . V 2 O 5 is a versatile material and also find extensive applications in chemical sensing, electro‐chromic and optical switching devices . V 2 O 5 in various forms as well as its nanocomposites are at present being widely employed as intercalation material in rechargeable batteries with mono/multivalent ions such as Li + , Na + , Mg 2+ ions, etc ,…”
Section: Introductionmentioning
confidence: 99%
“…60–80 nm exhibited photochromic change from yellow to green to pale blue. [ 205 ] The film was fabricated by mixing V powder with aq. H 2 O 2 solution dried then placed in a bath to obtain V‐IPA powder.…”
Section: Photochromic Applications Of Oxides and Hybrid Materials In Uv Sensingmentioning
confidence: 99%
“…These nanocomposites were used to improve sensing properties. Xiaobing et al [597] reported and their time dependence of the transmittance when coloring and bleaching [592]; (e) Schematic, SEM image and Nyquist plots of the carbon nanotube/V2O5 electrodes used in biosensing application [597].…”
Section: Vanadium Oxidementioning
confidence: 99%
“…Reproduced with permission of Elsevier (2018) [587], [589] and [597]; ACS publishing "Copyright (2018) American Chemical Society" [591]; and Royal Society of Chemistry (2018) [592].…”
Section: Vanadium Oxidementioning
confidence: 99%